INTEGRASI TEKNOLOGI DALAM ORGANISASI: TINJAUAN LITERATUR MENGENAI DAMPAK, TANTANGAN, DAN STRATEGI TRANSFORMASI DIGITAL - Rinda Nofiana; Achica Erika; Adelia Chicha N; Indita Ressa; Rauly Sijabat (Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
Digital transformation has become an essential requirement for organizations aiming to enhance efficiency, productivity, and competitiveness in the rapidly evolving digital era. The integration of advanced technologies offers various benefits, including streamlined operational processes, improved employee performance, and the promotion of organizational innovation. Nevertheless, digital transformation also presents several challenges, such as concerns over data security, resistance from employees toward change, and the substantial costs associated with implementation. This literature review examines the impacts, challenges, and strategies associated with digital transformation in organizational contexts. Findings indicate that successful transformation requires a clearly defined digital vision and strategy, the provision of comprehensive employee training to strengthen digital competencies, and the adoption of effective change management practices. Furthermore, organizations must prioritize robust data protection measures and invest in flexible systems capable of adapting to continuous technological advancements. The study contributes to the broader understanding of technology adoption by providing insights into practical strategies for managing digital transformation effectively. It offers valuable recommendations for organizational leaders seeking to leverage technological innovations while mitigating associated risks. Ultimately, digital transformation is not merely a technological shift but also a strategic initiative that demands organizational commitment, adaptability, and continuous capability development